Arrhythmias and COVID-19 infection - Chin, Ashley; Moses, Jane; Thornton, Andrew (SA Heart Journal, 2020)
Arrhythmias can be a clinical manifestation of COVID-19 infection. COVID-19 infection can also be a precipitant of known arrhythmias which can increase the risk of morbidity and mortality. Management of arrhythmias should generally follow standard guidelines of arrhythmia management. Catheter ablation in the midst of the COVID-19 pandemic should be limited to arrhythmias that are immediately life-threatening or which may affect prognosis in the short-term. Some novel treatments like chloroquine, hydroxychloroquine and azithromycin can prolong the QT interval and predispose patients to life-threatening arrhythmias.